Vibrational Spectroscopy-Based Chemometrics Analysis of Clinacanthus nutans Extracts after Postharvest Processing and Extract Effects on Cardiac C-Kit Cells - Vuanghao Lim; Hui Wen Chong; Nozlena Abdul Samad; Siti Aisyah Abd Ghafar; Ida Shazrina Ismail; Rafeezul Mohamed; Yoke Keong Yong; Chee Yuen Gan; Jun Jie Tan (Hindawi, 2024)
Indexed by Scopus/ERA